A-Z of nutritional supplements: dietary supplements, sports nutrition foods and ergogenic aids for health and performance: Part 46 - Deuster, P. A.; Hodgson, A. B.; Stear, S. J.; Burke, L. M.; Castell, L. M. (British Journal of Sports Medicine, 2013)
The concluding alphabetical part of our series, part 46, deals with just two topics for the letter `Z`. One of these, zinc monomethionine aspartate (ZMA), is a derivative of the other well-known supplement, zinc (Zn). Zn is widely used by both athletes and the general population.